Implementing Multimodal Approach To Enhance English Vocabulary Learning Of Fourth Grade Student - Fauzan Reza Fahlevi; Najwa Rizki Amalia; Diar Mukti Asri; Nisrina Farida Ramadhanti; Zaitun Qamariah; Hesty Widiastuty (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This study describes the implementation of a multimodal approach to enhance English vocabulary learning among fourth-grade students at a private Islamic elementary school in Palangka Raya. Method: A descriptive qualitative design was employed. Data were collected through classroom observations, student worksheets, reflection questionnaires, and documentation. Three worksheet types assessed vocabulary mastery, while observations and questionnaires explored student engagement. Practical Applications: Findings provide pedagogical insights for teachers designing interactive, multisensory English instruction that accommodates diverse learning styles and promotes active participation in primary education. Conclusion: The multimodal approach significantly improved students' vocabulary understanding, engagement, and enthusiasm. Integrating visual, auditory, and kinesthetic modes creates meaningful, enjoyable learning experiences, supporting effective vocabulary acquisition for young EFL learners.